A Cross- Sectional Study to Assess Health Status of Children in Urban Slum in Sagar City - Shrivastava, Ragini; Choudhary, Abhay Kumar; Nagar, Jagrati Kiran; Kaushal, Rituja (National Journal of Community Medicine, 2015)
Introduction: The future of the society depends on the quality of life of the children. Nutritional problems like protein energy malnutri- tion (PEM), anemia and vitamin A deficiency continue to plague a large proportion of Indian children. The diets and nutritional status of urban slum children in India is far away from being satisfactory. The major objective of this research is “to assess the health status of children of slum area. Method: The study comprised of 60 children of age group 1-10 from slum area in Sagar city. Detailed clinical examination, anthropometric measurement and Hemoglobin (Hb) estimation of all the children were done. Result: All the families were belonging to low socioeconomic group. Most of the children’s (53.44%) were partially immunized and 30% were not immunized only 16.7% were completely immunized. Total (50%) of children’s were malnourished out of that (13.36%) were had third degree malnutrition. And more than 80% children showed skin and hair changes and other signs of malnutrition. Most common mi- cronutrient deficiency found was anemia. Conclusion: Malnutrition is still a major public health problem in urban slums.